Material Inventory Control Analysis Using Safety Stock and Reorder Point Methods at PT. Hwaseung Bimaruna Indonesia - Muhammad Luthfi Aprian; Sutrisno; Apid Hapid Maksum; Muhammad Rafi Achsan; Naufal Rabbani Sumitra (Jurnal Serambi Engineering, 2026)
PT Hwaseung Bimaruna Indonesia is an automotive rubber component distribution company facing inventory control problems, as indicated by 33 materials categorized as Need Order in its Material Requirement Planning (MRP) system. This condition reflects a potential inventory shortage that may disrupt operational activities. This study aimed to identify materials with Need Order status, determine the required Safety Stock, and calculate the optimal Reorder Point (ROP) as a basis for inventory control. A quantitative approach was employed using the Safety Stock and Reorder Point methods. The research samples were selected through purposive sampling, focusing on five materials with the highest demand levels: 82130-I7000, 58737-BW200, 58738-BW200, 25415-I7000, and 26710-2M020. The data consisted of material demand records, inventory data, supplier lead time data, and company MRP data from January to May 2026. The results showed that the highest Safety Stock value was found for materials 58737-BW200 and 58738-BW200 at 1,889.29 units, while the lowest value was identified for materials 25415-I7000 and 26710-2M020 at 850.58 units. The highest Reorder Point value was obtained for materials 58737-BW200 and 58738-BW200 at 7,520.89 units, whereas the lowest value of 5,418.18 units was found for materials 25415-I7000 and 26710-2M020. The implementation of the Safety Stock and Reorder Point methods can assist the company in determining appropriate safety inventory levels and replenishment timing, thereby minimizing the risk of stockouts.